The business of tourism - Holloway, J. Christopher, ....-; Humphreys, Claire, ....- (Harlow : Pearson, 2016)
The tourism industry is in a constant state of flux, where trends and attitudes are frequently susceptible to outside influences, including factors such as technological and economic change. The Business of Tourism by Chris Holloway and Claire Humphreys is the ideal textbook to help readers not only understand these new changes but look at them with a critical eye and predict future trends. This book is an essential text for students of tourism management or travel and tourism. The historical context is combined with background theory and research, plus up-to-date international case studies. It examines in detail the tourism product, its impacts and the nature of the tourist, to provide the reader with a comprehensive understanding of the management of this important global industry. The result is a practical and relevant text for any student wishing to work in one of the many diverse sectors of the tourism industry.